KOMPOSISI JENIS DAN KELIMPAHAN IKAN DI PERAIRAN TELUK DORERI, MANOKWARI - Maria Massora (FMIPA Universitas Papua, 2007)
A study was done to search the composition and abundance of fish species in the waters of the Doreri Gulf the District of Manokwari, from September - October 2005. The fish catchments wash about 143 specimens consist of 49 species included in 23 families. The species of fish with a high abundance index consists of Nemipterus celebicus, Upeneus sundaicus, and Upeneus sulphureus. Those fishes have a high economic value in the market of Manokwari.